Community Development: The Challenges of Social Capital Strategy, Health Promotion, and Community Social Work - Irwandi Irwandi; Tri Yuliani (INDEV: International Journal of Islamic Community Development, 2022)
Research in the twenty-first century is turning toward community development and the value of community social work. The International Association of Schools of Social Work (IASSW) places work in society as the prevailing trend for the future of social work. Society is very important for people's lives and that, automatically leads to the need to have knowledge, skills and abilities (KSA) in community practice. This study discusses the common features of community social work, social capital, and health promotion methods. It will provide social opportunities for workers to improve and further develop their professional practice in the Community. The model in this article strongly recognizes the benefits and advantages of working with community development strategies, thereby contributing to healthy communities that were rebuild and generate social capital.